Pengaruh Jenis Mulsa dan Tinggi Bedengan terhadap Lingkungan Mikro Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.): The Effect of Types of Mulch and Bed Height on Micro Environment, the Growth and Yield of Shallots (Allium ascalonicum L.) - Herlina, Ninuk (Jurnal Hortikultura Indonesia, 2025)
Shallots (Allium ascalonicum L.) are an agricultural commodity with high economic value that cannot tolerate drought because of their short roots. Still, it cannot tolerate being in a place that is flooded with water. Efforts to manipulate the environment of shallot plants can be done by providing mulch and adjusting the height of the beds to improve soil air conditioning, as well as optimizing soil temperature and moisture. The research aims to obtain the best type of mulch and bed height that can increase the growth and yield of shallots. The study was carried out in January-April 2023 in Menggare Village, Slahung, Ponorogo, East Java. The research used RBD with 9 combination treatments of mulch and bed height (without mulch, straw, and silver black plastic mulch with bed heights of 30, 40, and 50 cm) and was repeated 3 times. Straw mulch and silver black plastic mulch can reduce soil temperature to a depth of 10 cm by 1.5-3.0 oC and 1.84 oC. Treatment of silver black plastic mulch 40 cm and 50 cm and 50 cm of straw mulch increased tuber production by 29.9, 34.6, and 31.9% compared to without mulch, 30 cm, which produces tubers 9.28 ton ha-1.Keywords: microclimate, silver black plastic mulch, shallot, soil temperature